SOSIALISASI PROGRAM IBM-PEMANFAATAN ENERGI TERBARUKAN (SOLAR CELL) UNTUK FASILITAS UMUM MASYARAKAT PEDESAAN - Jasa, L.; Ardana, I.P.; Weking, A.I. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Subdistrict Pupuan is one of the 10 subdistricts in the regency of Tabanan, located approximately 45 km to the West of the City of Tabanan regency. Subdistrict Pupuan is an area with huge potential to be developed in the field of agriculture and plantations, because in addition to the land fertile, rainfall is high enough and wide enough area. Subdistrict Pupuan, divided into 14 departments including the village and the village Padangan Batungsel village. Pempatan hamlet is one of the hamlets that are in Batungsel village with a population of approximately 175 families, while Padangan Dauh Tukad village is one of the hamlets of the village Padangan with a population of approximately 80 families, the majority of the villagers are farmers. Obstacles faced by rural communities over the years is the result produced agricultural population, especially the price is not stable harvest season, so the income of local residents to be reduced. The problems of transportation and communication are still lacking and tends to be difficult. Most people have enjoyed electricity from PT. PLN especially those living on the highway department Pupuan Tabanan, but not menjakau whole village because the conditions of topography and scattered settlements. Moreover, the new of constraints faced by the fuel price hike makes communities more difficult to meet the needs of everyday life. For that through the program IbM researchers want to try to disseminate the results of research related to renewable energy (solar cell), for an understanding of rural communities over the years, that electricity is derived from the PLN, while smber of renewable energy derived from nature that can be exploited independently has not been touched at all. Through a small group of two villages that fostered through this program diharafkan can deploy science and technology related to renewable energy (solar cell) among the people so that knowledge can be useful for the welfare of rural communities.